Safety and Tolerability of Cariprazine in Patients with Schizophrenia: A Pooled Analysis of Eight Phase II/III Studies [Corrigendum] - Barabássy Á (Dove Medical Press, 2021)
Barabássy Á, Sebe B, Acsai K, et al. Neuropsychiatr Dis Treat. 2021;17:957–970. The authors have advised that there are errors in the first row of Table 5 on page 963. Cariprazine 4.5 mg column, the value “1 (0.0)” should read “1 (0.2)”. Cariprazine 6 mg column, “2 (0.0)” should read “2 (0.3)”. Total 1.5-6 mg/d column, “0” should read “3 (0.1)”. The authors apologize for these errors. Read the original article